CPP301 Software Engineering Practice August/September 1998 - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 1998)
Bachelor of Computer Science (Hons) External Degree USM Programme (In Collaboration with Universiti Sains Malaysia) August/September 1998 CPP301 Software Engineering Practice Time : [3 hours] INSTRUCTIONS TO CANDIDATES: Please ensure that this examination paper contains FIVE questions in FOUR printed pages before you start the examination. Answer FOUR questions only. Answer any TWO questions from Section A and answer ALL questions in Section B. On each page, write only your Student ID.